(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of a competitive test of early-ripening egg-plant lines L-9/13 and L-7/13, conducted in 2014-2016 at the Surkhandarya scientific experimental station. According to the given information, the highest total yield was observed on the L-7 line and it was 69.0 t / hec, which is 15.9% higher than the comparative variety and the L-9 line was identified as a new aubergine variety with early ripening, round fruit shape, resistant to bulging nematodes and from 2019 onwards, agricultural crops have been handed over to the State Variety Testing Commission.